PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP PENGANGGURAN DAN KEMISKINAN DI KABUPATEN BATANG - ISTIQOMAH; Hermawan Adinugraha, Hendri (Bapelitbang Kabupaten Batang, 2024)
Economic growth and inflation are continuous. Economic growth followed by inflation has the same curve; if economic growth rises, inflation will rise, and vice versa. This study aims to determine how the relationship and how much influence economic growth and inflation have on unemployment and poverty in Batang Regency. This research uses descriptive qualitative research by using open and reactive observation methods to collect secondary data from relevant sources from observable people and actors, both in writing and orally. This research also uses data sources from the Batang Regency Statistics Agency. The results show that economic growth and inflation have positive and negative influences. Unemployment has a significant influence on the poverty rate.Keywords: Economic Growth, Inflation, Unemployment, Poverty